Pengembangan Model Pembelajaran Natural Circuit Play sebagai Upaya Meningkatkan Keterampilan Motorik Halus Anak - Ritonga, Rizki Amaliah; Masra Tangse, Uswatun Hasanah (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
Fine motor skills are a very important aspect of development in a child's daily life. The purpose of this study was to test the effectiveness of a Natural Circuit Play learning model in an effort to improve fine motor skills of children aged 4-5 years. The type of research used is the development approach (research and development). The subjects of this research trial involved children aged 4-5 years throughout South Labuhanbatu Regency involving 123 children. The data collection instruments used in this study were assessment form sheets, interviews and points of view. The effectiveness of the Natural Circuit Play learning model was analyzed using the Kruskal Wallis test at a significance level of 0.05. The results of this study indicate that there is a significant change in children's fine motor skills by applying the Natural Circuit Play model as evidenced by the Kruskal Wallis test which shows a significance value of 0.00